Dystocia in Small Ruminants – A Retrospective Analysis - B. Srilatha; K. Prabhakar Rao; K.Manoj; Gs. Haritha; P. Ramesh; B. Prakash Kumar (The Indian Veterinary Journal, 2024)
A brief retrospective study of seventy small ruminants with history of dystocia was evaluated over a period of 10 months. The clinical cases of dystocia were categorized into fetal (n=44) and maternal causes (n=26). Fetal causes include faulty disposition (n=35) and oversized fetus (n=9) while, maternal causes include incomplete cervical dilatation (n=16) and uterine torsion (n=10). Sixty animals were relieved from dystocia by gentle traction and the rest 10 animals were subjected to caesarean section by lower left flank laparohysterotomy. In our study, it was observed that the major cause of dystocia due to fetal and maternal origin were faulty disposition (79.54%) and incomplete cervical dilatation (61.53%), respectively.